Blood-Brain Barrier Cellular Responses Toward Organophosphates: Natural Compensatory Processes and Exogenous Interventions to Rescue Barrier Properties - Ravid, Orly; Elhaik Goldman, Shirin; Macheto, David; Bresler, Yael; De Oliveira, Raquel Ines; Liraz-Zaltsman, Sigal; Gosselet, Fabien; Dehouck, Lucie; Beeri, Michal Schnaider; Cooper, Itzik (Frontiers in Cellular Neuroscience, 2018)
Organophosphorus compounds (OPs) are highly toxic chemicals widely used as pesticides (e.g. paraoxon (PX)- the active metabolite of the insecticide parathion) and as chemical warfare nerve agents. Blood-brain barrier (BBB) leakage has been shown in rodents exposed to PX, which is an organophosphate oxon. In this study, we investigated the cellular mechanisms involved in BBB reaction after acute exposure to PX in an established in-vitro BBB system made of stem-cell derived, human brain-like endothelial cells (BLECs) together with brain pericytes that closely mimic the in-vivo BBB. Our results show that PX directly affects the BBB in-vitro both at toxic and non-toxic concentrations by attenuating tight junctional protein (TJ) expression and that only above a certain threshold the paracellular barrier integrity is compromised. Below this threshold, BLECs exhibit a morphological coping mechanism in which they enlarge their cell area thus preventing the formation of meaningful intercellular gaps and maintaining barrier integrity. Importantly, we demonstrate that reversal of the apoptotic cell death induced by PX, by a pan-caspase-inhibitor ZVAD-FMK (ZVAD) can reduce PX-induced cell death and elevate cell area but do not prevent the induced BBB permeability, implying that TJ complex functionality is hindered. This is corroborated by formation of reactive oxygen species (ROS) at all toxic concentrations of PX and which are even higher with ZVAD. We suggest that while lower levels of ROS can induce compensating mechanisms, higher PX-induced oxidative stress levels interfere with barrier integrity.